Methods and results of skills demand and supply forecasting - the case of Germany - Maier, Tobias [Verfasser] (My University, 2012)
This article gives an introduction to the methods of the QUBE (Beruf und Qualifikation in der Zukunft - Occupation and Qualification in the Future) project carried out by the Federal Institute for Vocational Education and Training (BIBB) and the Institute for Employment Research (IAB) with the Fraunhofer Institute for Applied Information Technology (FIT) and the Institute of Economic Structures Research (GWS). In this project, model calculations for future developments in labour supply and requirements in accordance with four qualification levels and 12 main occupational fields/54 occupational fields were drawn up. The author then compares the QUBE results with those of the Cedefop forecast of "Skills supply and demand in Europe". The main finding of this comparison is that even though the taxonomy and methods of the QUBE project differ from those of the Cedefop forecasts, both projections rely on similar databases and forecast similar trends for skills demand and supply development in Germany. (BIBB-Doku)
Keywords: Arbeitsmarktentwicklung; Qualifikationsentwicklung; Berufsfeld; Prognose; BIBB/IAB-Erhebung